Level of dengue preventive practices and associated factors in a Malaysian residential area during the COVID-19 pandemic: a crosssectional study - Mashudi, Dina Nurfarahin; Ahmad, Norliza; Mohd Said, Salmiah (Public Library of Science, 2022)
Background Dengue fever is a mosquito-borne viral infection that is endemic in more than 100 countries and has the highest incidence among infectious diseases in Malaysia. The increase of dengue fever cases during the COVID-19 pandemic and the movement control order (MCO) highlighted the necessity to assess the dengue preventive practices among the population. Thus, this study aimed to determine the level of dengue preventive practices and its associated factors among residents in a residential area in Johor, Malaysia during the COVID-19 pandemic. Method A community-based cross-sectional study was conducted on 303 respondents from a Johor residential area between May and June 2021. A validated self-administered questionnaire was created using google forms and distributed to the respondents via WhatsApp. The questionnaire consisted of three sections: (i) Sociodemographic characteristics and history of dengue fever, (ii) dengue preventive practices, and (iii) six constructs of the Health Belief Model (HBM). The association between the dependent and independent variables were examined using multiple logistic regression with a significant level set at less than 0.05. Result About half of the respondents have a good level of dengue preventive practices. Respondents with a history of dengue fever (aOR = 2.1, 95% CI: 1.1-4.2, p = 0.033), low perceived susceptibility (aOR = 1.8, 95% CI: 1.1-3.0, p = 0.018), high self-efficacy (aOR = 1.7, 95% CI: 1.0-2.8, p = 0.045), and high cues to take action (aOR = 2.5, 95% CI: 1.5-4.2, p < 0.001) had higher odds of practicing good dengue preventive measures. Conclusion This study demonstrated a moderate level of dengue preventive practices during the COVID-19 pandemic. Therefore, a stronger dengue control programme is recommended by focusing on cues to take action, self-efficacy, and recruiting those with a history of dengue fever to assist health authorities in promoting good dengue preventive practices in the community.